The impact of career guidance (CG) for career choice (CC) in the secondary schools of Sepitsi Circuit in lLebowakgomo District, Limpopo Province - Nong, Tlou William (My University, 2016)
The aim of this study is to assess the impact of career guidance for career choice in the secondary schools of Sepitsi Circuit in Lebowakgomo District, Limpopo Province. The total number of secondary schools in the Circuit is twelve (12), with 20 Life Orientation Educators (LOEs) and 275 Grade 12 Learners (GR12Ls). All schools are public schools having the same features of rural and previously disadvantaged communities’ context. The study was conducted during examination time and therefore co-operation both in the part of learners and educators was not at the maximum as expected. The research is evaluative in nature as the researcher sought to assess the effectiveness of Career Choice (CC) as influenced by the implementation of Career Guidance (CG). The primary data were collected by means of two categories of questionnaires for mostly close-ended questions and open-ended questions for Grade 12 Learner (GR12L) respondents and Life Orientation Educator (LOE) participants respectively. The findings show that CG is not given the necessary attention at secondary schools as GR12Ls and LOEs struggle to understand obvious CG concepts. This research project focuses on the value of such a study both to explain how Career Guidance need to be taken as the mother of all subjects in schools as it is the nucleus in the realization of the main aim of every country’s education system, participating fully in the world of work for socio-economic growth. The study’s recommendations concluded that Career Guidance, which is part of Life Orientation (LO), should be given the status of a full subject in our schools.
Thesis (M. Dev.) -- University of Limpopo, 2016
Keywords: Career guidance; Career choice; Vocational guidance.